Social support and self-efficacy multiply mediate the relationship between medical coping style and resilience in patients with type A aortic dissection - Hong, Miaoxuan; Zhang, Rong; Zhu, Jin; Tan, Wenxuan (Frontiers in Psychiatry, 2023)
Background: Previous research has shown that medical coping modes are associated with resilience in cardiovascular disease patients. However, postoperatively, the mechanism underlying this association in Stanford type A aortic dissection patients is poorly understood. Objective: This study investigated the mediating effects of social support and self-efficacy on the relationship between medical coping modes and resilience in Stanford type A aortic dissection patients postoperatively. Methods: We assessed 125 patients after surgery for Stanford type A aortic dissection using the Medical Coping Modes Questionnaire, the General Self-Efficacy Scale, the Social Support Rating Scale, and the Connor–Davidson Resilience Scale. Structural equation modeling with AMOS (v.24) was used to test the hypothesized model with multiple mediators. Both direct and mediational effects (through social support and self-efficacy) of medical coping modes on resilience outcomes were examined. Results: The mean Connor–Davidson Resilience Scale score was 63.78 ± 12.29. Confrontation, social support, and self-efficacy correlated with resilience (r = 0.40, 0.23, 0.72, respectively; all p < 0.01). In multiple mediation models, social support independently (effect = 0.11; 95% confidence interval [CI], 0.04–0.27) and social support and self-efficacy serially (effect = 0.06; 95% CI, 0.02–0.14) mediated the association of confrontation with resilience maintenance, accounting for 57.89% and 10.53% of the total effect, respectively. Conclusions: Social support and self-efficacy were multiple mediators of the relationship between confrontation and resilience. Interventions designed to facilitate confrontation and subsequently increase social support and self-efficacy may be useful to increase resilience in Stanford type A aortic dissection patients.